Ecology and biocontrol options of the leaf miner, liriomyza huidobrensis, on potatoes in the Western Cape province - Mugala, Thabu (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScConsEcol)--Stellenbosch University, 2021.